EVALUASI PENATAUSAHAAN BARANG MILIK DAERAH MENURUT PP NO. 27 TAHUN 2014 PADA BADAN PENGELOLA KEUANGAN DAN ASET DAERAH KOTA MANADO - Supit, Priscila T.; Tinangon, Jantje J.; Mawikere, Lidia M. (JURNAL RISET AKUNTANSI GOING CONCERN, 2017)
Administration is the activity of managing assets that includes bookkeeping, inventorying and the reporting of regionâs asset according to the terms and condition that applies. Administration has an important role in policy making, as all policy will be better and more suitable with accurate and valid data that comes from the act of administration. The main objective of this research is to find out whether the managing of regionals assets towards the Financial and Asset management Agency of the City of Manado is according to Governmentâs Regulation No. 27 Year 2014. The method of analysis that is used on this research is the qualitative descriptive method. The result of this research shows that the administration of regionalâs assets towards the Financial and Asset management Agency of the City of Manado has been implemented but not according to Governmentâs Regulation No. 27 Year 2014. The cause of the reporting mechanism failing to follow the Governmentâs regulation No. 27 Year 2014 is due to the failure of Asset management Agency of the City of Manado not having a Goods Authority. Therefore the Asset management Agency of the City of Manado needs to create the Department of Regional Technical Implementation so that the head of the department will be the Goods Authority and will be in charge of creating the semester and yearly reports. Keywords: Administration, Regionâs Asset According